2011
DOI: 10.1186/1750-2187-6-13
|View full text |Cite
|
Sign up to set email alerts
|

E4BP4 facilitates glucocorticoid-evoked apoptosis of human leukemic CEM cells via upregulation of Bim

Abstract: BackgroundSynthetic GCs serve as therapeutic agents for some lymphoid leukemias because of their ability to induce transcriptional changes via the GC receptor (GR) and trigger apoptosis. Upregulation of the BH3-only member of Bcl-2 family proteins, Bim, has been shown to be essential for GC-evoked apoptosis of leukemic lymphoblasts. Using human T cell leukemic sister clones CEM-C7-14 and CEM-C1-15, we have previously shown that the bZIP transcriptional repressor, E4BP4, is preferentially upregulated by GCs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 58 publications
1
20
0
Order By: Relevance
“…We have previously demonstrated that E4BP4-dependent upregulation of Bim contributes to GC-evoked apoptosis of human leukemic CEM cells, using a cell line derived from the GC-resistant CEM C1-15 cells that ectopically expresses mouse E4BP4 (CEM C1-15mE#3) [15]. Here, we have extended our studies to evaluate the role of E4BP4 in GC-dependent regulation of genes whose protein products are known to crosstalk with E4BP4, and genes implicated in apoptosis.…”
Section: Resultsmentioning
confidence: 78%
See 4 more Smart Citations
“…We have previously demonstrated that E4BP4-dependent upregulation of Bim contributes to GC-evoked apoptosis of human leukemic CEM cells, using a cell line derived from the GC-resistant CEM C1-15 cells that ectopically expresses mouse E4BP4 (CEM C1-15mE#3) [15]. Here, we have extended our studies to evaluate the role of E4BP4 in GC-dependent regulation of genes whose protein products are known to crosstalk with E4BP4, and genes implicated in apoptosis.…”
Section: Resultsmentioning
confidence: 78%
“…CEM C1-15 cells express functional GR, which has been shown to be transcriptionally active with a blunted response to GC stimulus, hence modest regulation of GC-dependent genes is to be expected (4). Bim is a well-known mediator of GC-evoked apoptosis of lymphoid leukemic cells [14], and we have shown that its expression correlates with E4BP4 expression [15] (Figure 2A). BIRC3 or IAP-1 (Inhibitor of Apoptosis-1) is known to bind to TRAFs ( T umor necrosis factor R eceptor A ssociated F actors) and inhibit apoptosis by interfering with activation of caspases.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations